2001
DOI: 10.1002/clc.4960241008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of left atrial size and function on P‐wave dispersion: A study in patients with paroxysmal atrial fibrillation

Abstract: It was concluded that deltaP increased in patients with PAF and normal LA size. In controls with increased LA size, deltaP increased but did not reach the levels attained in patients with PAF. The AEF was decreased in patients with PAF but was preserved in those without PAF. These findings can be explained by the changes in LA microarchitecture which concurrently decreased atrial myocardial contraction, increased deltaP, and predisposed to PAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 15 publications
2
38
0
4
Order By: Relevance
“…Interobserver variability was 3 ± 4% and intraobserver variability was 1 ± 3%. It has been reported that P max and PD are associated with age, 28 left ventricular systolic function, 29 left atrium size 30 and increased sympathetic activity. 31 In our study there was no significant difference between the two groups in terms of these measures.…”
Section: Discussionmentioning
confidence: 99%
“…Interobserver variability was 3 ± 4% and intraobserver variability was 1 ± 3%. It has been reported that P max and PD are associated with age, 28 left ventricular systolic function, 29 left atrium size 30 and increased sympathetic activity. 31 In our study there was no significant difference between the two groups in terms of these measures.…”
Section: Discussionmentioning
confidence: 99%
“…Bu elektrofizyolojik özelliklerin, yüzey EKG'ye, P dalga süresinin uzaması ve PDD' nun artması şeklinde yansıdığı düşünülmektedir (19). Sol atriyal volüm değiş-kenliğinin de PDD' na neden olabileceği bilinmektedir (20). Atriyal aritmileri, özellikle paroksismal AF' yi öngörmek için PDD' nin kullanılabileceği bildirilmiştir (19)(20)(21).…”
Section: Discussionunclassified
“…Sol atriyal volüm değiş-kenliğinin de PDD' na neden olabileceği bilinmektedir (20). Atriyal aritmileri, özellikle paroksismal AF' yi öngörmek için PDD' nin kullanılabileceği bildirilmiştir (19)(20)(21). Bu tekniğin değişik hasta popülasyonlarında AF öngörücüsü olarak kullanılabilece-ğine ait birçok yayın vardır.…”
Section: Discussionunclassified
“…12 In another study it was seen that PD was significantly prolonged in cases with paroxysmal AF, in contrast to cases without paroxysmal AF, even though left atrium sizes of both groups were equal. 13 It was shown that DM is an independent and strong risk factor for development of AF. 14,15 The frequency of AF development is 1.4-2.1-fold higher in cases with DM than cases without DM.…”
Section: Discussionmentioning
confidence: 99%